Reposisi Desa Dalam Sistem Ketatanegaraan Indonesia: Analisis Kewenangan Dan Otonomi Daerah - Moh. Arief Erawan; Mohamad Rasyid Ridho (Universitas Suryakancana, 2025)
AbstractVillages constitute the most fundamental level of government in Indonesia and possess original rights that existed prior to the establishment of the state. Although villages have received constitutional recognition under Article 18B of the 1945 Constitution and normative reinforcement through Law Number 6 of 2014 on Villages, the implementation of village authority continues to face significant challenges. These include regulatory disharmony with Law Number 23 of 2014 on Regional Government, intervention by regional authorities, and overlapping competencies that undermine village autonomy. This condition renders the study on the repositioning of villages within Indonesia’s constitutional system urgent. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that, normatively, village authority reflects the principles of recognition and subsidiarity; however, in practice, villages are still treated as subordinate administrative units. This study concludes that villages must be repositioned as sui generis governmental entities through regulatory harmonization and a clearer allocation of authority between central and regional governments within the framework of the Unitary State of the Republic of Indonesia.AbstrakDesa merupakan entitas pemerintahan paling dasar yang memiliki hak asal-usul dan telah diakui secara konstitusional melalui Pasal 18B Undang-Undang Dasar 1945 serta diperkuat oleh Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Namun, dalam praktiknya penyelenggaraan kewenangan desa masih menghadapi persoalan disharmoni regulasi dengan Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah, intervensi pemerintah daerah, dan tumpang tindih kewenangan yang berdampak pada lemahnya otonomi desa. Kondisi ini menjadikan penelitian mengenai reposisi desa dalam sistem ketatanegaraan Indonesia bersifat urgen. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa secara normatif kewenangan desa telah mencerminkan prinsip rekognisi dan subsidiaritas, namun implementasinya masih menempatkan desa sebagai unit administratif subordinatif. Simpulan penelitian menegaskan perlunya reposisi desa sebagai entitas pemerintahan sui generis melalui harmonisasi regulasi dan penataan hubungan kewenangan pusat dan daerah dalam kerangka Negara Kesatuan Republik Indonesia.